Increased serum human epididymis protein 4 is associated with disease activity and systemic involvement in pediatric-onset systemic lupus erythematosus - Liu, Chenxi; Yan, Lingyi; Zhang, Menglan; Duan, Yifei; Luo, Jie; Liu, Zhijun; Liu, Ting; Tong, Jiyu; Jiang, Yongmei (Frontiers in Immunology, 2024)
We aimed to investigate human epididymis protein 4 (HE4) as a potential biomarker in patients with pediatric-onset systemic lupus erythematosus (pSLE), particularly on the association of serum HE4 levels with disease activity and other laboratory tests.We included 137 patients with pSLE and 75 age-and sex-matched healthy controls (HCs).Serum HE4 level was measured by a chemiluminescent microparticle on an Abbott ARCHITECT i2000SR Immunoassay Analyzer. Comparisons between groups were performed using the independent Student t-test, Mann-Whitney U test, Chi-square test, or Fisher's exact test, as appropriate. We also determined the relationships between HE4 and clinical parameters and evaluated disease activity using SLE Disease Activity Index (SLEDAI) and renal SLEDAI (rSLEDAI).Serum HE4 levels in patients with pSLE (44.6 pmol/L; IQR, 32.5-73.5) were significantly higher than those in HCs (38.9 pmol/L; IQR, 34-46.1). HE4 levels were significantly higher in moderate to severe disease activities (57.4 pmol/L, IQR 37.7-164.5) than in mild disease activities (38.8 pmol/L, IQR 30.1-48.5) or HCs (38.9 pmol/L, IQR 34.0-46.1), as well as in active renal disease activities (77.2 pmol/L, IQR 47.4-224.1) than in inactive renal disease 2 activities (36.1 pmol/L, IQR 27.8-46.7). The ROC curve analysis showed that HE4 could discriminate pSLE with renal (AUC, 0.717; 95% CI, 0.632-0.801), hematological (AUC, 0.740; 95% CI, 0.648-0.831), and cardiovascular involvement (AUC:0.775, 95% CI 0.669-0.880).Serum HE4 levels significantly correlated with several indicators related to renal morbidity, such as creatinine, blood urea nitrogen, uric acid, cystatin C, urine protein/24 h, etc.Serum HE4 levels in pSLE were elevated and highly associated with disease activity and systemic involvement, indicating HE4 as a potential biomarker for pSLE.